The association of obesity with post-cesarean inpatient opioid consumption - Strong, Abigail L.; Tvina, Alina; Harrison, Rachel K.; Watkins, Jayla; Afreen, Esha; Tsaih, Shirng-Wern; Palatnik, Anna (International Journal of Obesity, 2024)
Background Obesity and prescription opioid misuse are important public health concerns in the United States. A common intersection occurs when women with obesity undergo cesarean birth and receive narcotic medications for postpartum pain. Objective To examine the association between obesity and inpatient opioid use after cesarean birth. Methods A retrospective cohort study of patients that underwent cesarean birth in 2015–2018. Primary outcome was post-cesarean delivery opioid consumption starting 24 h after delivery measured as morphine milliequivalents per hour (MME/h). Secondary outcome was MME/h consumption in the highest quartile of all subjects. Opioid consumption was compared between three BMI groups: non-obese BMI 18.5–29.9 kg/m 2 ; obese BMI 30.0–39.9 kg/m 2 ; and morbidly obese BMI ≥ 40.0 kg/m 2 using univariable and multivariable analyses. Results Of 1620 patients meeting inclusion criteria, 496 (30.6%) were in the non-obese group, 753 (46.5%) were in the obese group, and 371 (22.9%) were in the morbidly obese group. In the univariate analysis, patients with obesity and morbid obesity required higher MME/h than patients in the non-obese group [1.3 MME/h (IQR 0.1, 2.4) vs. 1.6 MME/h (IQR 0.5, 2.8) vs. 1.8 MME/h (IQR 0.8, 2.9), for non-obese, obese, and morbidly obese groups respectively, p < 0.001]. In the multivariable analysis, this association did not persist. In contrast, subjects in the obese and morbidly obese groups were more likely to be in the highest quartile of MME/h opioid consumption compared with those in the non-obese group (23.5% vs. 48.1% vs. 28.4%, p < 0.001, respectively); with aOR 1.42 (95% CI 1.07–1.89, p = 0.016) and aOR 1.60 (95% CI 1.16–2.22, p = 0.005) for patients with obesity and morbid obesity, respectively. Conclusion Maternal obesity was not associated with higher hourly MME consumption during inpatient stay after cesarean birth. However, patients with obesity and morbid obesity were significantly more likely to be in the top quartile of MME hourly consumption.